Android-Based National University Logistic Information System Using Sdlc Model Waterfall Method: Android-Based National University Logistic Information System Using Sdlc Model Waterfall Method - Rian Aditia; Agung Triayudi; Novi Dian Nathasia (Jurnal Mantik, 2020)
The utilization of computerized information systems is very important, especially in higher education. The existence of a computerized information system makes a process of processing important data that can be arranged and stored properly and makes it easier to find data when needed. Included in the logistics department of the National University which still needs the support of a system that is able to facilitate the processing of data entry and exit of goods contained in the National University logistics warehouse. The purpose of this research is to be able to alleviate the work on logistics in terms of streamlining the use of time, energy, and costs incurred in recording and making logistical reports. Then an android-based logistics information system will be built using the information system approach method used in making and developing applications, namely the system development life cycle (SDLC) method using the waterfall model. The construction of this system was made using sublime text 3 and MySQL as its database. This system will be able to manage the data of incoming and outgoing goods and also perform data searches on a mobile basis using an Android smartphone. With the creation of a logistics information system at the Android-based National University, it is hoped that it can help and speed up the work in processing logistical data that will be used as material for making reports.